2023
DOI: 10.3389/fendo.2023.1270518
|View full text |Cite
|
Sign up to set email alerts
|

Global incidence and prevalence of differentiated thyroid cancer in childhood: systematic review and meta-analysis

Mariacarla Moleti,
Tommaso Aversa,
Salvatore Crisafulli
et al.

Abstract: ObjectiveDifferentiated thyroid cancer (DTC) is rare in childhood and adolescence although it represents the most frequent endocrine malignancy in this population. DTC includes both papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC). Most pediatric DTCs are PTCs, while FTCs are rare. To date, no systematic reviews on the global epidemiology of pediatric and adolescent DTC have been published. This systematic review and meta-analysis aims to estimate the overall incidence and prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Generally speaking, both thyroid autotransplantation studies on animals and those on humans have shown good results regarding the viability and functionality of the transplant, although information on the outcome remains poor. As the trend of malignant pathology in pediatric age patients is increasing all over the world, an alternative solution to lifelong hormone replacement therapy in specific categories of patients who underwent thyroidectomy could be that of autotransplanting cryopreserved thyroid tissue in selected patients [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, both thyroid autotransplantation studies on animals and those on humans have shown good results regarding the viability and functionality of the transplant, although information on the outcome remains poor. As the trend of malignant pathology in pediatric age patients is increasing all over the world, an alternative solution to lifelong hormone replacement therapy in specific categories of patients who underwent thyroidectomy could be that of autotransplanting cryopreserved thyroid tissue in selected patients [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Well-differentiated cancer of the thyroid gland is one of the most common types of endocrine neoplasias, representing the ninth most frequent malignancy worldwide [1]. During the last decades, its incidence has increased approximately by 300%, affecting a wide spectrum of patients, including adolescents and young adults, while the female-to-male ratio is estimated to be 1:2 [2,3]. Despite its increasing prevalence, the prognosis of thyroid cancer is rather good, with an estimated five-year survival rate ranging between 80% and 90% in European countries [4].…”
Section: Introductionmentioning
confidence: 99%